Mechanisms of visibility of rurality and border areas in Usme - Meneses-Baez, Alba Lucia; Casas-Matiz, Elvia Isabel (Frontiers in Built Environment, 2024)
Introduction: The visibility of rurality contributes to optimizing the planning and administrative management processes of the territories by providing contextualized information about the relationship of the inhabitants with the area under study. The objective of this research is to identify the mechanisms of visibility of rurality in Usme, a locality in Bogotá, Colombia. Methods: A case study was carried out using a mixed methodology. Based on a literature review, conceptual categories that support the visibility of rurality were formulated, and based on them, a perception survey addressed to the peasant leaders of Usme was designed. The survey contained 22 questions that inquired about socio-demographic data, citizen participation, roles of the inhabitants, participation scenarios, conditions, institutions, opportunities for improvement, and the needs and processes of the locality; the questions were multiple-choice with a single answer and open-ended. The survey was sent to 50 peasant leaders, of whom 36 responded (13 men, 21 women, and 2 LGBTIQ), who were residents of low (25), medium (3), and high (8) localities in the rural zone of Usme. Using the ATLAS.ti program, a frequency analysis was carried out for the multiple-choice questions and the textual data, as well as a content analysis of deductive and emergent categories; then, a nomological network on the mechanisms of visibility was constructed. Results: Findings show that participants understand rurality visibility mechanisms in terms of five dimensions: spaces of visibility, dimensions of rurality, forms of participation, places of participation, and types of impact. Discussion: The delimitation and definition of the dimensions that constitute the mechanisms of rurality visibility in the borders contribute to the designing of effective strategies to improve the conditions of the inhabitants of this area, as well as their participation in increasing the impact and coverage of the institutions of the territory, aiming to improve the quality of life of the inhabitants of the area. We concluded that, in order for this to happen, it is necessary to have community empowerment and social co-responsibility among the community, civil institutions, and government.